A Taguchi-based Kansei engineering study of mobile phones at product design stage - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2013)
This article is aimed at applying Taguchi method in Kansei engineering and explores a way to integrate it into an industrial product design stage. Emotional customer needs are derived using Kansei image word pairs. The Taguchi-based approach is validated by a case study with mobile phones. Experimental work in implementing the proposed approach was able to suggest design attributes of a mobile phone that are essential to be considered at the product design stage to satisfy the customers' expectations and hence to increase the company's sales.
Keywords: Kansei engineering; mobile phones; Taguchi method; product design; USABILITY EVALUATION; FORM DESIGN; SYSTEM